Exploring the effectiveness of evidence-based methods to measure and improve offenders’ engagement in treatment - Alemohammad, Mehd (2017)
Treatment non-engagement in forensic settings is a major problem, which has been associated with increased recidivism and higher costs. This thesis aimed to evaluate existing methods of enhancing engagement, test an innovative motivational strategy to enhance engagement, and critically evaluate an effective measurement of engagement. Firstly, a systematic review and a meta-analysis of Randomised Controlled Trials (RCTs) was conducted to evaluate the effectiveness of Motivational Interviewing (MI). It was concluded that MI may be effective for engagement, but measurement of engagement is inconsistent and unreliable. Therefore, MI was integrated into a novel training package for staff in addition to a promising readiness model and a motivational assessment. The feasibility of such intervention was investigated for probation staff, and its preliminary effect on probationers’ group engagement was assessed using the Group Engagement Measure (GEM-27; Macgowan, 1997). Findings showed while it is generally feasible to implement such an intervention, it is possible that short training in such settings might not be as impactful due to organisational issues, staff burnout and external influences. However, GEM-27 showed promise with regards to being able to measure offender engagement. After critically reviewing its characteristics, with further research and modifications, it was concluded GEM could be widely used in forensic settings. In conclusion, advancements in evidence-based measures of engagement and forensic specific strategies to enhance offender engagement are the initial steps towards developing a comprehensive theory of offender engagement and increasing treatment effectiveness.